2001
DOI: 10.1159/000050037
|View full text |Cite
|
Sign up to set email alerts
|

HBV Core Particles as a Carrier for B Cell/T Cell Epitopes

Abstract: In the middle 80s, recombinant hepatitis B virus cores (HBc) gave onset to icosahedral virus-like particles (VLPs) as a basic class of non-infectious carriers of foreign immunological epitopes. The recombinant HBc particles were used to display immunodominant epitopes of hepatitis B, C, and E virus, human rhinovirus, papillomavirus, hantavirus, and influenza virus, human and simian immunodeficiency virus, bovine and feline leukemia virus, foot-and-mouth disease virus, murine cytomegalovirus and poliovirus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
199
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(208 citation statements)
references
References 103 publications
5
199
0
4
Order By: Relevance
“…HBc fusion proteins often maintain the self-assembling ability and display inserted foreign epitopes on the tips of particle spikes if they are inserted into the MIR. 6 However, folding and capsid formations of the chimeric proteins are not always achieved easily, and the insert size and composition often are limitation factors in this process due to the conformational stress. Earlier it was shown that failure of some chimeric proteins to assemble into VLPs could be explained by the length of the insert; 120 amino acids are usually accepted as a maximum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBc fusion proteins often maintain the self-assembling ability and display inserted foreign epitopes on the tips of particle spikes if they are inserted into the MIR. 6 However, folding and capsid formations of the chimeric proteins are not always achieved easily, and the insert size and composition often are limitation factors in this process due to the conformational stress. Earlier it was shown that failure of some chimeric proteins to assemble into VLPs could be explained by the length of the insert; 120 amino acids are usually accepted as a maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Dimer clustering of two HBc monomers produces spikes on the surface of the capsid, and the loop region located on top of these spikes (residues 78 -83) is the major target of the humoral response, i.e., major immunodominant region (MIR). 6,7 Generally HBc-based VLPs have been used as an epitope presentation system in vaccine design and antigen presentation studies. [8][9][10][11] On the other hand, the ability of HBc to incorporate peptides of different origin may be useful in the development of NPs for different application.…”
mentioning
confidence: 99%
“…HBc⌬ vector carrying all HBc T-helper cell and cytotoxic-T-lymphocyte (CTL) epitopes but lacking the C-terminal arginine-rich region was chosen for epitope insertions as an efficient vaccine scaffold. The HBc MIR region and C terminus of such shortened HBcs were selected as the best places for insertions of HBV and HCV epitopes, respectively (30).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the MIR is generally accepted as the target site of choice for insertion of foreign epitopes (30). The other widely accepted site for insertions is C-terminal position 144, a short stretch after the e2 epitope.…”
mentioning
confidence: 99%
See 1 more Smart Citation